Evaluation of a bacteriocinogenic Lactobacillus plantarum strain on the microbiological characteristics of “Alheira de Vitela” - Ariana Macieira; Helena Albano; Miguel Pinto; Raquel Linheiro; Joana Barbosa; Paula Teixeira (AIMS Agriculture and Food, 2019)
Lactic Acid Bacteria (LAB) and their bacteriocins can be successfully used as natural preservatives in meat products. This work aimed to investigate the effect of fresh and lyophilized starter cultures of an autochthonous bacteriocinogenic LAB strain (Lactobacillus plantarum ST153Ch: bac + culture) on the microbiological characteristics of “Alheira”, a traditional Portuguese smoked product. “Alheira” with the addition of fresh or lyophilized culture (ca. 108 cfu/g) and “Alheira” control (no bacteriocinogenic culture added) were produced by an industrial meat company. The antilisterial activity of this culture in this food matrix was investigated, with some samples being inoculated with Listeria monocytogenes (ca. 105 cfu/g). Detection of L. monocytogenes, Salmonella spp., sulphite reducing clostridia, Yersinia enterocolitica and enumeration of L. monocytogenes, Staphylococcus aureus, Bacillus cereus, Escherichia coli, Enterobacteriaceae, lactic acid bacteria, yeasts and moulds were performed immediately after production and at 3, 7, 15, 21, 28, 60 and 90 days of storage at 4 ℃, according to ISO methodologies. Also, a 16S rRNA Gene Analysis was performed of the microbial communities of “Alheira” with and without the lyophilized bacteriocinogenic culture. Pathogenic and indicator organisms were not detected or were below acceptable levels in all samples. LAB counts increased during storage and reached similar values after 15 days (ca. 1010 cfu/g) in all samples. There was a clear trend for a higher reduction of L. monocytogenes in the presence of the bioprotective culture, more pronounced during the initial 15 days of storage. From the analysis of the microbial communities of samples of “Alheiras” at different stages of fermentation, Leuconostocaceae and Lactobacillaceae predominated in all the samples and Lactobacillus was the genus more prevalent in “Alheiras” after 60 days of storage with the addition of bacteriocinogenic culture.